CYTOTOXIC PROTEIN FROM Trichosanthes cucumerina L. var anguina (L.) Haines - Churiyah Zafrollah; WAHONO SUMARYONO (SEAMEO BIOTROP, 2010)
Three proteins were discovered, they were: TF2 from fruit, TS3 from seed and TR3 from root of Trichosanthes cucumerina L. var anguina (L.) Haines by extraction with Phosphate Buffer Saline (PBS). The proteins were precipitated using 80% saturated ammonium sulphate and then were dialysed using cellophane. Furthermore, the dialysate was fractionated through gel filtration chromatography. The highest protein yield was 1.109%, resulted from TS3, then 0.356% from TR3, and the lowest was 0.014% from TF2. Characterization of the proteins using SDS-PAGE indicated that all of the protein fractions showed more than one sub unit molecular masses (Mr) in the range of 16 - 29 kDa. The toxicity (LC50) of proteins on brine shrimp lethality test were within range of 19 µg/ml - 25 µg/ml. The cytotoxicities of the TR3 and TS3 proteins on cancer cell line indicated that both of the active proteins inhibit proliferation of HeLa and K-562 cells with IC50 up to 45 µg/ml. Keywords : Trichosanthes cucumerina L. var anguina (L.), plant part, protein, yield, toxicity, cytotoxicity, molecular mass.